1991
DOI: 10.1159/000116626
|View full text |Cite
|
Sign up to set email alerts
|

Manganese, Selenium and Other Trace Elements in Spinal Cord, Liver and Bone in Motor Neurone Disease

Abstract: Trace element levels were measured by neutron activation analysis in spinal cord, liver and bone of 7 control patients dying of non-neurological disease and 15 patients dying of motor neurone disease (MND). The concentration of selenium was significantly elevated in the cervical cord, liver and bone in the MND group. Although spinal cord manganese levels were increased at both the cervical and thoracic levels, the hepatic concentration was reduced in the MND patients. These findings are discussed in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Some studies in other locations found increased Mn levels in brain, spinal cord, and muscle from ALS patients (Kurlander and Patten, 1979; Mitchell et al, 1991; Miyata et al, 1983) while others did not (Kihira et al, 1990; Pierce-Ruhland and Patten, 1980). Most of these studies were small, however, and the observed changes in Mn levels may reflect tissue degeneration.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies in other locations found increased Mn levels in brain, spinal cord, and muscle from ALS patients (Kurlander and Patten, 1979; Mitchell et al, 1991; Miyata et al, 1983) while others did not (Kihira et al, 1990; Pierce-Ruhland and Patten, 1980). Most of these studies were small, however, and the observed changes in Mn levels may reflect tissue degeneration.…”
Section: Discussionmentioning
confidence: 97%
“…Mitchell et al [51] report a significant elevation of selenium within the cervical cords (as well as livers and bones) of motor neuron disease patients. However, a similar trend is absent in the thoracic and lumbar spines.…”
Section: Seleniummentioning
confidence: 99%
“…ALS arising in a patient affected by liver cirrhosis, a condition known to imply Mn overload due to impaired biliary excretion of the metal [174], has also been observed [175]. Mn overload has been reported in pathological and analytical studies of Guamanian and sporadic ALS cases [176, 177, 178, 179, 180]; the last two studies also showed an increase in MnSOD levels in motor neurons of affected subjects. Indeed, environmental data from the Western Pacific endemic foci of ALS, including the Kii peninsula in Japan, support a role for Mn in its prevalence in these areas [181, 182] and contribute to what is generally called “the mineral hypothesis” of the ALS/Parkinson’s Dementia Complex (ALS/PDC).…”
Section: Mn and Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%